Seismotectonic features in the Northern Aegean sea - ΜΠΑΡΑΚΟΥ, Θ.; ΔΕΛΗΜΠΑΣΗΣ, Ν.; ΒΟΥΛΓΑΡΗΣ, Ν.; BAIER, Β. (Bulletin of the Geological Society of Greece, 2001)
The analysis and processing of 1135 microearthquakes, recorded during the time period May 1993 – December 1994, indicated that the North Aegean Trough and the Trough of Skyros are the boundaries of, respectively, the NW and SE side of a tectonic Block in the shape of a trapezium, whose large base is the NW one. ΝW of the island of Lemnos, the North Aegean Trough changes direction from ENE-WSW to NE-SW. This point operates as a joint, on either side of which a differentiation of the areas is visible. In the SW of the troughs, two seismic gaps, which seem to be connected to a presently shaping channel of a NW-SE trend, were observed. The two southern branches of the North Anatolia Fault will constitute, in future, the northern and southern boundary of the Trough of Skyros. The migration of earthquakes in the North Aegean Sea follows a right lateral direction, however this direction changes to left lateral east of Chios Island.